Pasteurella multocida cellulitis and possible septic arthritis of the knee after exposure to dog saliva after a recent total knee arthroplasty - Natallia Suvorava; Leopoldo Dobronski; Richard Winn (Southwest Respiratory and Critical Care Chronicles, 2017)
Prosthetic joint replacement occurs frequently. Complications of prosthetic joint replacements include bleeding, mechanical disruption, persistent pain, and infection. Infectious complications can occur early or late, measured in hours to days or months to years. The microorganism profiles vary depending on whether infection is early or late. Factors related to wound care have a significant role in the development of wound infection and coincident infection of the prosthesis. We report a wound infection and possible septic arthritis with septic shock due to Pasteurella multocida; symptoms and signs of joint involvement were noted but aspiration of the joint was declined by the orthopedic surgery service due to concerns about joint contamination from the overlying cellulitis. Blood cultures were sterile. The wound had been licked by her pet dogs on numerous occasions. Ultimately the infection was eradicated with antimicrobial agents, and the septic shock resolved.